Antiplatelet therapy impact on immunological status in patients with recent onset of angina pectoris - Zavalskaya, T.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The study involved 42 patients with recent onset of stenocardia (ROS) aged 45 to 65 and 18 clinically healthy individuals. Determination of populations and subpopulations of lymphocytes was performed by monoclonal antibodies. Determination of immunoglobulins Ig G, Ig A, Ig M and circulating immune complexes (CIC) in blood serum was performed by the Mancini method. The results showed that basic treatment of patients with ROS by clopidogrel with aspirin (aspigrel) combination is more effective than the basic treatment that included only clopidogrel, which was indicated by the positive trend of more indicators of patients' immune status. Full normalization of cellular and humoral immunity indices wasn't found in patients with ROS after treatment, which is possibly associated with a marked inhibition of the overall immune response in these patients and the need to find new drugs.